Relationship between senior assistant of extra curricular leadership styles and job satisfaction of extracurricular teachers in Malaysia - Abdul Halim, Norhaily; Basri, Ramli; Yusof, Aminuddin; Hassan, Aminuddin (Human Resource Management Academic Research Society, 2019)
This study was carried out to determine extracurricular teachers’ perception of their Senior Assistant of Extracurricular leadership styles (transformational, transactional and passive avoidant) and their level of job satisfaction. In addition, the study investigated the relationship between Senior Assistant of Extracurricular leadership styles and extracurricular teachers’ job satisfaction based on the perception of 381 extracurricular teachers from 42 regular secondary schools throughout Malaysia. Data was collected using Avolio and Bass (1995) Multifactor Leadership Questionnaire (5X Short Form) and The Job Satisfaction Survey by Spector (1994). The result indicated that extracurricular teachers in this study perceived the overall transformational leadership and transactional leadership practiced by their Extracurricular Senior Assistant are at a high level while the overall passive avoidant leadership practiced by their Extracurricular Senior Assistant is at a low level. Descriptive analysis also shows that extracurricular teachers in this study perceived their overall job satisfaction at a moderate level. In addition, the finding reveals that both transformational and transactional leadership have a positive significant relationship with teachers’ job satisfaction while passive avoidant leadership has a negative significant relationship with job satisfaction.